In air we dream - Liu, Pinyao; Riecke, Bernhard E.; Kitson, Alexandra J.; Stepanova, Katerina (Recto VRso Vancouver 2020, 2021)
Flying dreams have the potential to evoke a feeling of empowerment and self-transcendent emotions (STEs). However, these exceptional dreaming experiences remain infrequent. In this experience you will set off on a dream-like journey with magical floating ability, and seek the source of life that connects every being.
Keywords: Riecke; Riecke_2021; VR demo; VR exhibition; alex-kitson; bernhard-riecke; curated-exhibit; demonstration; katerina-stepanova; pinyao-liu; proj--in-air-we-dream; talkWithoutPaper; thesis-related